Blockade of JAK2 protects mice against hypoxia‐induced pulmonary arterial hypertension by repressing pulmonary arterial smooth muscle cell proliferation. (14th January 2020) - Zhang, Lei; Wang, Yi; Wu, Guorao; Rao, Lizong; Wei, Yanqiu; Yue, Huihui; Yuan, Ting; Yang, Ping; Xiong, Fei; Zhang, Shu; Zhou, Qing; Chen, Zhishui; et al.
Abstract: Objectives: Hypoxia is an important risk factor for pulmonary arterial remodelling in pulmonary arterial hypertension (PAH), and the Janus kinase 2 (JAK2) is believed to be involved in this process. In the present report, we aimed to investigate the role of JAK2 in vascular smooth muscle cells during the course of PAH. Methods: Smooth muscle cell (SMC)‐specific Jak2 deficient mice and their littermate controls were subjected to normobaric normoxic or hypoxic (10% O2 ) challenges for 28 days to monitor the development of PAH, respectively. To further elucidate the potential mechanisms whereby JAK2 influences pulmonary vascular remodelling, a selective JAK2 inhibitor was applied to pre‐treat human pulmonary arterial smooth muscle cells (HPASMCs) for 1 hour followed by 24‐hour hypoxic exposure. Results: Mice with hypoxia‐induced PAH were characterized by the altered JAK2/STAT3 activity in pulmonary artery smooth muscle cells. Therefore, induction of Jak2 deficiency in SMCs protected mice from hypoxia‐induced increase of right ventricular systolic pressure (RVSP), right ventricular hypertrophy and pulmonary vascular remodelling. Particularly, loss of Jak2 significantly attenuated chronic hypoxia‐induced PASMC proliferation in the lungs. Similarly, blockade of JAK2 by its inhibitor, TG‐101348, suppressed hypoxia‐induced human PASMC proliferation. Upon hypoxia‐induced activation, JAK2 phosphorylated signal transducer and activator of transcription 3 (STAT3), which then bound to the CCNA2 promoter to transcribe cyclin A2 expression, thereby promoting PASMC proliferation. Conclusions: Our studies support that JAK2 could be a culprit contributing to the pulmonary vascular remodelling, and therefore, it could be a viable target for prevention and treatment of PAH in clinical settings.